P022 Transcriptional biomarkers for vedolizumab therapy response in patients with moderate to severe Ulcerative Colitis. (21st January 2022) - Arosa García, L; Camba-Gómez, M; Calviño-Suárez, C; Bastón-Rey, I; Ferreiro-Iglesias, R; Porto, M; Nieto-García, L; Domínguez-Muñoz, J E; Barreiro-de Acosta, M; Conde-Aranda, J
Abstract: Background: Vedolizumab is one of the current treatments for patients with Inflammatory Bowel Disease (IBD). The efficacy and safety, together with its gut specificity, make this drug an appealing therapeutic option for IBD patients with moderate to severe disease. However, as observed for other biologic treatments, a significant proportion of patients do not have an initial response to vedolizumab treatment. Currently, there is a lack of reliable biomarkers for vedolizumab treatment response, although this would help to palliate the socioeconomic costs derived from this disease. For that reason, the primary aim of this study is to establish the basis for the search of transcriptional factors associated with vedolizumab treatment response. Methods: For the realization of this study, we collected blood samples from responder and non-responder Ulcerative Colitis (UC) patients treated with vedolizumab. The clinical response was measured using the Partial Mayo Score. The frequencies of different immune system populations were analysed by flow cytometry. Moreover, we measured the transcriptional levels of several genes in peripheral blood mononuclear cells (PBMC) by RT-qPCR. These experimental procedures were performed at baseline (T0) and after 14 weeks of follow-up (T14). Results: We enrolled nine patients with an average age of 46.25±11.71, of which seven were previously treated with anti-TNF therapy. Our results show a specific pattern in responder and non-responder patients in the percentages of different innate and adaptive immune cell populations at T0 versus T14. Similarly, we observed a significant reduction in the expression of some chemokines (i.e., CCL25) and pro-resolutive factors (i.e., ANNEXIN A1) at T14 versus T0 in PBMCs from vedolizumab responder patients, which was not observed in non-responder patients. Conclusion: Our data suggest that the frequencies of certain immune populations are associated with the response to vedolizumab treatment. In the same way, we found that specific transcripts are modulated in response to this α4β7 integrin antibodies in PBMCs. Therefore, we found a solid system to search for vedolizumab therapy response markers using low invasive techniques.